2015
DOI: 10.18805/lr.v0iof.6788
|View full text |Cite
|
Sign up to set email alerts
|

Variation in phosphorus accumulation in groundnut cultivars as influenced by water salinity

Abstract: Soil salinity remains an obvious abiotic stress that changes the behavior of nutrient accumulation in crop plants. Phosphorus being a key element in determining crop growth and economic yield, its uptake in plant parts varies under saline condition. Hence an experiment was conducted to assess the changing phosphorus content in eight groundnut cultivars,were grown in a field trial having in-built soil salinity developed with 0.5, 2.0, 4.0 and 6.0 dS m -1 of saline irrigations (EC iw ). Root-P was observed to ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
(10 reference statements)
1
2
0
Order By: Relevance
“…This may have happened due to supplemental irrigation of saline water resulting in the accumulation of salt in the dry/summer season, but that partially leached out in the following kharif season as a result of ample rainfall. A similar increase in soil EC values in long-term salinity trials with groundnut was earlier reported (Bhaduri et al, 2016;Bhaduri et al, 2020). Saline vertisols, dominated by salinization and sodification processes, occupying a large share of salt-affected area (2.22 M ha) are present in Gujarat and productivity of these soils was found to be poor even at low salinity due to the typical physico-chemical characteristics (Chinchmalatpure et al, 2018).…”
Section: Build-up Of Soil Salinitysupporting
confidence: 88%
“…This may have happened due to supplemental irrigation of saline water resulting in the accumulation of salt in the dry/summer season, but that partially leached out in the following kharif season as a result of ample rainfall. A similar increase in soil EC values in long-term salinity trials with groundnut was earlier reported (Bhaduri et al, 2016;Bhaduri et al, 2020). Saline vertisols, dominated by salinization and sodification processes, occupying a large share of salt-affected area (2.22 M ha) are present in Gujarat and productivity of these soils was found to be poor even at low salinity due to the typical physico-chemical characteristics (Chinchmalatpure et al, 2018).…”
Section: Build-up Of Soil Salinitysupporting
confidence: 88%
“…Saline has a negative effect on the health status of plants, inhibits the growth processes, decreases the photosynthesis efficiency, leads to physiological drought. Saline and sodication are abiotic soil factors which pose a serious threat to soil fertility and thus affect soil production (Bhaduri et al 2016). To understand the soil system ecology, one must know the activity of soil microorganisms and soil enzymes which show a fast reaction to slight changes in soil environment.…”
Section: Introductionmentioning
confidence: 99%
“…The conceptual model of Shen et al (2011) depicted a great scope for root/rhizosphere and soil-based nutrient managements for improving P-use efficiency and crop productivity in intensive agriculture. P-uptake of peanut plants was also found to cultivar-specific under similar experimental conditions since cultivars TG 37A and GG 7 accumulated more leaf-P and root-P under long-term salinity trial, when salinity played a crucial role in determining P-uptake (Bhaduri et al, 2016). Poor soil-P availability, high fixation, inconsistent and Phosphorus is an important element for plant growth, essentially required for energy transfer and nucleic acids (Marschner, 1995).…”
Section: Introductionmentioning
confidence: 95%